2015
DOI: 10.2147/ijn.s76501
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in magnetic resonance imaging: from simple to dual contrast agents

Abstract: Magnetic resonance imaging (MRI) has become one of the most widely used and powerful tools for noninvasive clinical diagnosis owing to its high degree of soft tissue contrast, spatial resolution, and depth of penetration. MRI signal intensity is related to the relaxation times ( T 1 , spin–lattice relaxation and T 2 , spin–spin relaxation) of in vivo water protons. To increase contrast, various inorganic nanoparticles and complexes (the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(124 citation statements)
references
References 101 publications
2
106
0
3
Order By: Relevance
“…MRI pre-scans were taken before injection of EuCF-RPV (G4) or EuCF-PCL plus NRPV (G5) to establish a baseline signal and representative pre-scans are shown in Fig.5B. MRI was chosen as the first modality because of its superior spatial resolution, which provides the most accurate information about the localization of these particles in soft tissues[43]. Post-injection MR images were acquired 2 and 5 days after particle intravenous administration (Fig.5B).…”
Section: Resultsmentioning
confidence: 99%
“…MRI pre-scans were taken before injection of EuCF-RPV (G4) or EuCF-PCL plus NRPV (G5) to establish a baseline signal and representative pre-scans are shown in Fig.5B. MRI was chosen as the first modality because of its superior spatial resolution, which provides the most accurate information about the localization of these particles in soft tissues[43]. Post-injection MR images were acquired 2 and 5 days after particle intravenous administration (Fig.5B).…”
Section: Resultsmentioning
confidence: 99%
“…There is a need to formulate standard procedures to control and compare different NPs in terms of cytotoxic effects and uptake efficiency. The effects of iron oxide NPs should be carefully evaluated on cultured cells prior to assessing their clinical potential in cell transplantation research 27,48,99,113…”
Section: Factors Enhancing the Efficiency Of Iron Oxide Npsmentioning
confidence: 99%
“…NP-based contrast agents for MRI have advantages over conventional contrast agents due to improved sensitivity and prolonged blood circulation time. [35] Qualitative and quantitative information on NP distribution could be obtained from MRI generated transverse ( R 2 or 1/ T 2 ) or longitudinal relaxation rates ( R 1 or 1/ T 1 ) maps with the assumption that the changes in relaxation rates are dominated by the changes in NP concentration. [36, 37] In one study, the distribution of Gd 3+ conjugated polymeric NPs in brains showed enhanced T 1 signal.…”
Section: Nanoparticles For Targeting and Imaging Of Breast Cancer mentioning
confidence: 99%